A Chloroacetate‐Caged Fluorescein Chemodosimeter for Imaging Cysteine/Homocysteine in Living Cells. Issue 5 (3rd January 2013) - Zhu, Baocun; Zhao, Yunzhou; Zhou, Qi; Zhang, Bing; Liu, Lunying; Du, Bin; Zhang, Xiaoling
Abstract: A chloroacetate‐caged fluorescein chemodosimeter (CACFC) employing a double molecular recognition mechanism was designed and synthesized to selectively detect cysteine (Cys) and homocysteine (Hcy) over glutathione (GSH) and other amino acids. The results showed that CACFC could serve as a "naked‐eye" indicator, and quantitatively detect Cys and Hcy with a detection limit of 4 μM (Cys) and 7 μM (Hcy). Additionally, CACFC was successfully applied to the fluorescence imaging of Cys and Hcy in living cells. The mechanism of the reaction between CACFC and Cys/Hcy was confirmed by ESI‐MS and fluorescence spectroscopic analysis to involve a conjugate substitution/cyclization sequence. We highlight the simplicity of the design and synthesis and show that its combined properties, such as high specificity, high sensitivity, fast response, quantitative detection and real time Cys and Hcy imaging in living cells should find applications in imaging and biomedical fields. Abstract : A chloroacetate‐caged fluorescein chemodosimeter (CACFC) employing a double molecular recognition mechanism was designed and synthesized to selectively detect cysteine (Cys) and homocysteine (Hcy) over glutathione (GSH) and other amino acids.